Analysis Method for Ground Settlement Induced by Ultra-Deep Excavation in Hangzhou Soft Clay Considering Time-Space Effect - XIONG Yifan, YING Hongwei, ZHANG Jinhong, CHENG Kang, LI Binghe (Shanghai Jiaotong Daxue xuebao)
The PLAXIS 3D software and the soft soil creep model were used to establish a 3D numerical model of the B2 excavation within an ultra-deep excavation group, allowing for analysis of the effects of time-space factors on ground settlements. Then, the complementary error function and trilinear model were introduced. After that, the numerical results were used to correct the complementary error function. Finally, a rapid approach was proposed for predicting ground settlements while accounting for the temporal and spatial influences. The results indicate that soft soil creep not only causes additional wall deflections resulting in soil settlements but also induces soil settlements independent of these deflections. The impact of ignoring soft soil creep on prediction of ground settlement is not weaker than that of wall deflections. The excavation area determines the construction duration when the excavation depth and rate are identical, impacting ground settlements induced by soft soil creep.